Rahmatan lil ‘Alamin as a Pedagogical Paradigm in Islamic Education: A Literature Review - Rahmadi Agus Setiawan (Atha Publishing Globalindo, 2026)
Although ethical values are central to Islamic education, many foundational Islamic concepts remain framed primarily in normative-theological terms, with limited pedagogical development. One such concept is rahmatan lil ‘alamin, which is frequently invoked to promote inclusivity, moderation, and compassion but rarely articulated as a coherent educational paradigm. This conceptual gap limits its pedagogical relevance in contemporary and plural educational contexts. This article aims to reconstruct rahmatan lil ‘alamin as a pedagogical paradigm in Islamic education by translating its ethical foundations into educational principles. Using a qualitative literature review, the study examines Qur’anic and Prophetic sources alongside Islamic education scholarship and international literature on religious and values-based education. The analysis identifies four interrelated pedagogical principles through which rahmatan lil ‘alamin can be operationalized: humanization of education, justice and inclusivity, orientation toward public good and social responsibility, and integrative epistemology of learning. These principles position learners as ethical agents, affirm diversity as a pedagogical resource, connect learning with social engagement, and integrate religious knowledge with contemporary disciplines. This study contributes by reframing rahmatan lil ‘alamin from a moral ideal into a pedagogical framework and by situating Islamic education within broader global debates on inclusive and humane education.